Níveis de vitamina D3 para frangos de corte - Tainá Silva Brandão Lopes (2020)
This work was conducted with the purpose of evaluating the effects of reduced levels of vitamin D3 (cholecalciferol) on the performance and bone quality of broilers up to 35 days of age. Diets for the initial phase (1 to 14 days) and growth (15 to 35 days) were used ad libidum. The diets were isonutritive and the vitamin supplement provided adequate amounts of all vitamins, except vitamin D3. The levels of vitamin D3 used were: A group, 0 IU / Kg in both phases; B group, 625 IU / Kg of in the initial phase and 500 IU / Kg in the growth phase, representing 25% of the inclusion used commercially; C group, 1.250 IU / Kg in the initial phase and 1.000 IU / Kg in the growth phase, representing 50% of the inclusion used commercially; D group, 1.875 IU / Kg in the initial phase and 1.500 IU / Kg in the growth phase representing 75% of the inclusion used commercially; E group, 2.500 IU / Kg in the initial phase and 2.000 IU / Kg in the growth phase, representing 100% of the inclusion used commercially. The experimental design was completely randomized with 5 treatments of 6 repetitions each. 360 one-day-old Cobb® chicks were distributed in 30 cages containing 12 birds each. The birds were weekly evaluated for feed intake (CR), body weight (BW), conversion (WC) and viability (V). At 21 and 35 days of age, a repetitive chicken was euthanized and the tibiae and femurs removed and dissected. The bones were evaluated for the percentage of dry matter, mineral matter, calcium, phosphorus, bone strength and density. At 35 days of age, the bones underwent histopathological evaluation for macro and microscopic morphological evaluation. At the end of the experiment, the birds were evaluated for varus and valgus deformities. For the performance variables, percentage of calcium, phosphorus, mineral matter, dry matter and bone strength, there was a linear effect increasing up to the supplementation levels of approximately 25% of inclusion. In the histopathological evaluation, only the group that received a diet with 75% of the inclusion of vitamin D3 presented bone tissue within the normal range, the other groups showed alterations compatible with osteopenia and osteopetrosis. The observed results showed that for isonutritive diets it is not necessary to use the commercial levels currently practiced, since the reduction by up to 75% and 25% guaranteed, respectively, the zootechnical performance and bone quality during the evaluated period.